Synchrony of Dengue Incidence in Ho Chi Minh City and Bangkok. - Cuong Hoang Quoc; Salje Henrik; Rodriguez-Barraquer Isabel; Yoon In-Kyu; Nguyen Van Vinh Chau; Nguyen Thanh Hung; Ha Manh Tuan; Phan Trong Lan; Bridget Willis; Ananda Nisalak; Siripen Kalayanarooj; Derek A T Cummings; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Ho Chi Minh City and Bangkok are highly dengue endemic. The extent to which disease patterns are attributable to local versus regional dynamics remains unclear. To address this gap we compared key transmission parameters across the locations. METHODS AND PRINCIPAL FINDINGS:We used 2003-2009 age-stratified case data to inform catalytic transmission models. Further, we compared the spatial clustering of serotypes within each city. We found that annual case numbers were highly consistent across the two cities (correlation of 0.77, 95% CI: 0.74-0.79) as was the annual force of infection (correlation of 0.57, 95% CI: 0.46-0.68). Serotypes were less similar with serotype-specific correlations ranging from 0.65 for DENV1 to -0.14 for DENV4. Significant spatial clustering of serotypes was observed in HCMC at distances <500m, similar to previous observations from Bangkok. DISCUSSIONS:Dengue dynamics are comparable across these two hubs. Low correlation in serotype distribution suggests that similar built environments, vector populations and climate, rather than viral flow drives these observations.